Sensitive and Low‐background Electrochemical Immunosensor Employing Glucose Dehydrogenase and 1, 10‐Phenanthroline‐5, 6‐dione. Issue 8 (21st May 2021) - Jiaul Haque, Al‐Monsur; Kwon, Jungwook; Kim, Jihyeon; Kim, Gyeongho; Lee, Nam‐Sihk; Ho Yoon, Young; Yang, Haesik
Abstract: We report a sensitive electrochemical immunosensor with a low electrochemical background level, which results from electrochemical‐enzymatic (EN) redox cycling based on mediated electrochemical oxidation of an electro‐inactive reductant (glucose) at 0.0 V. The EN redox cycling employs flavin adenine dinucleotide‐dependent glucose dehydrogenase and 1, 10‐phenanthroline‐5, 6‐dione (PD). When PD was compared with five common quinone‐based electron mediators, PD enabled the highest signal‐to‐background ratio, due to a very low electrochemical background level. When EN redox cycling was applied to a sandwich‐type immunosensor, parathyroid hormone (PTH) in serum could be detected with a very low detection limit of ∼0.1 pg/mL. Abstract :